The Role of Agricultural Extension Workers in Empowering Farmer Groups - Rifaldi, Muh Yusril; Akbar,; Sahlan,; Jumiati,; Saleh, Muh Ikmal (JURNAL AGRIBISAINS, 2025)
The role of agricultural extension workers is crucial in the process of empowering farmer groups. In reality, the level of farmer participation and group independence remains low. This condition is caused by the lack of farmers’ trust in extension workers due to their limited direct involvement in agricultural field activities. This study aims to examine the role of agricultural extension agents in empowering farmer groups in Kajang District, Bulukumba Regency. Respondents were selected using a random sampling technique, with a total sample of 24 farmer group members. The data were analyzed using a quantitative descriptive method to identify and measure the level of extension agents’ roles based on predetermined indicators. The results reveal four main indicators of the extension agents’ roles: as educators, analyzers, consultants, and organizers. The role as educator obtained an average score of 2.16, the role as analyzer 2.28, the role as consultant 2.34, and the role as organizer 2.23. All these scores fall into the “moderately significant role” category. These findings indicate that the role of agricultural extension agents in empowering farmer groups in Tambangan Village still needs to be improved across all aspects. Extension agents are expected to be more active, innovative, and evenly involved in facilitating farmer group activities, including knowledge transfer, problem analysis, solution provision, and group organization. Optimizing these roles is expected to enhance the effectiveness of empowerment programs so that their benefits can be fully experienced by all group members. Therefore, strengthening the capacity of extension agents is a key factor in promoting the independence and sustainability of farmer groups in the study area.